Cultural Symbol Reconstruction: Innovative Expression of Traditional Leather Craftsmanship in Modern Product Design - Kaiyu MO; Jing DING (Pige Kexue Yu Gongcheng)
Traditional leather craftsmanship, as a cultural symbol carrying historical and cultural information, regional and ethnic features, has important value and significance in modern product design. Designers can carry out multi-dimensional innovations in terms of material, technique, shape and function, and explore the application of materials and techniques, expand the modernity of shape and function, coordinate the expression of cultural connotation and modern aesthetics, and combine innovation in technology and craftsmanship to achieve the organic integration of traditional leather craft and modern design. The innovative expression of traditional leather craft in modern product design is not only the inheritance of skills, but also the reconstruction of cultural symbols, showing unlimited innovative potential.